Economic analysis of consumer choices based on rice attributes in the food markets of West Africa—the case of Benin - Naseem, A.; Mhlanga, S.; Diagne, A.; Ygué Adegbola, P.; Midingoyi, G.S.K. (Springer, 2013)
The focus of this study was to investigate consumer preferences for various attributes of rice marketed in Benin. Consumer choice theory postulates that products are consumed not for themselves, but for the characteristics they possess that satisfy consumers’ greater liking of one attribute over another. In the case of rice, quality attributes, as incentives for both producers and consumers, have important price implications. In this study, we empirically analyzed the relationship between the price paid by consumers for their choice of rice and its attributes in the markets of Benin using hedonic pricing and discrete choice models of demand. We used data collected from rice-consuming households in four major provinces of Benin, in both rural and urban areas, during 2006. The results of this econometric estimation indicated that there was considerable variability in consumer preferences for different rice attributes across the regions studied. Nevertheless, consumers paid a premium price for observable attributes, such as grain size and breakage. In addition, both urban and rural consumers preferred imported and parboiled rice to domestic and raw rice. The study results showed that implicit prices paid by consumers for both domestic and imported rice were based on quality attributes. These findings have important implications for future breeding programs aimed at making domestic rice more competitive with imported rice.